Volumetric analysis of Attalea funifera Mart. (Arecaceae) pollen in bee pollen samples from the low southern coast of Bahia, Brazil - Alves, Rodolfo de França (2019)
The volumetric analysis of Attalea funifera Mart. (Arecaceae) pollen was carried out. Commercialized bee pollen samples were collected from May to November 2014 in Nilo Peçanha, Bahia State. The pollen samples were identified and quantified in order to determine their botanical origin and to analyze the importance of A. funifera to bee pollen composition, under the volumetric aspect. The pollen spectrum was composed of 23 pollen types distributed in 13 botanical families, especially Fabaceae, Euphorbiaceae and Asteraceae. The most frequent pollen type was Mimosa pudica, but the volumetric analyzes indicated A. funifera as the most important in the constitution of the pollen collected. Therefore, based on the volume (93,974.70 μm³), the potential of A. funifera pollen is verified in bee pollen samples and, consequently, the importance of volumetric analysis in addition to quantitative and frequency analyzes.